A PROPHETIC STUDY ON EARTHQUAKE - Tangngareng, Tasmin; Hasbullah, Hasbullah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2019)
The phenomenon of earthquakes has become part of human’s dark story within the history of the past people, in the current millennial era and it will still apply even to the end of the world. This article will discuss a study of earthquakes contained in the hadith of the Prophet (peace be upon him). In the history of prophethood, this phenomenon has occurred in Medina and even repeatedly experienced by the Prophet p.b.u.h. together with his faithful companions. The complex discourse will come to vision with the implementation of two contrasting technical dialogues on the subject, namely those of the theological and the scientific views. The complexity of the convergence of the two lies in the detail that each had a circumstance in the prophetic era and is mentioned in the words of the Prophet p.b.u.h. The theological view believes that an earthquake is a punishment from the Creator owing to the decadence of morality in a society, whereas in a scientific perspective, an earthquake occurs because of the shift of the earth’s plate which results in vibrations. Additionally, in the theological perspective, earthquakes are seen as parts of eschatology since there is a sign of their occurrence in the future mentioned in the hadith of the Prophet p.b.u.h. As for the theory of science, it is supported by the message of the Prophet p.b.u.h. that there is a geographical area with a high potential of earthquake strikes. Thus the discourse of the earthquake which has become a part of people’s lives, as is also mentioned in the Prophet’s hadith, will certainly come to pass for two main reasons, firstly it is related to the normative theological perspective and secondly, it is in accordance with the scientific studies. ملخصأصبحت ظاهرة الزلزال جزءًا من الجانب المظلم من حياة الناس، في تاريخ الشعوب السابقة حتى عصر الألفية الحالي وحتى يوم القيامة. سوف يناقش هذا المقال دراسة الزلازل الواردة في حديث النبي الكريم، وقد حدثت هذه الظاهرة في التاريخ النبوي في المدينة المنورة بل مرارًا وتكرارًا من قِبل النبي الكريم. مع الاصدقاء. سوف يولد خطاب معقد مع التناقض بين اثنين من الحوارات العلمية، وهما الرؤية اللاهوتية والنهج العلمي. تعقيد تقارب كل منهم له مصدر حدث في العصر النبوي أو مذكور في كلمات الرسول. وجهة النظر اللاهوتية تعتقد أن الزلزال كعقوبة من الخالق كان سببه الضرر المعنوي للمجتمع. بينما في منظور علمي، تحدث الزلازل بسبب تحول لوحات الأرض التي تسبب الاهتزاز. لا يزال في نظر اللاهوت، أصبح الزلزال جزءا من الاعتقاد في الغيب لأنه كان هناك علامة في الحديث النبوي. أن الزلزال سيحدث في المستقبل، في حين أن وجهة النظر العلمية تدعمها رسالة النبي. أن هناك منطقة جغرافية معرضة للزلازل. وهكذا يمكن أن يحدث خطاب الزلزال الذي تندمج مع الحياة المجتمعية في خطاب الحديث بالتأكيد لسببين رئيسيين، يتعلقان باللاهوت المعياري ولا يمكن فصلهما عن الدراسات العلمية.الكلمات المفتاحية: الحديث ، الزلزال ، الآراء اللاهوتية والعلمية Fenomena gempa bumi telah menjadi bagian dari sisi kelam kehidupan masyarakat, baik dalam sejarah umat-umat terdahulu sampai era milenial sekarang dan bahkan hingga menjelan hari kiamat. Artikel ini akan membahas sebuah studi gempa bumi yang terdapat dalam hadis Nabi saw., dalam sejarah kenabian fenomena ini pernah terjadi di Madinah bahkan berkali-kali dialami oleh Nabi saw. bersama dengan para sahabat. Jenis penelitian ini tergolong kualitatif dengan menggunakan pendekatan ilmu hadis, teologi, sosio-historis dan saintifik. Diskursus yang rumit pun akan lahir dengan pertentangan antara dua dialog keilmuan, yaitu pandangan teologi dengan pendekatan ilmiah (saintifik). Kerumitan konvergensi keduanya masing-masing mempunyai embrio yang pernah terjadi di era kenabian maupun disebut dalam sabda Sang Rasul. Pandangan teologi meyakini bahwa gempa sebagai azab dari Sang Pencipta disebabkan karena dekadansi moralitas dalam sebuah masyarakat. Sedangkan dalam perspektif saintis, gempa terjadi karena pergeseran lempeng bumi yang mengakibatkan sebuah getaran. Masih dalam pandangan teologi, gempa bumi menjadi bagian dari eskatologi karena terdapat sebuah isyarat dalam hadis Nabi saw. bahwa gempa akan terjadi di masa yang akan datang, sementara pandangan sains yang didukung oleh pesan Nabi saw. bahwa terdapat sebuah daerah geografis yang rawan terjadi gempa bumi. Dengan demikian wacana gempa bumi yang telah menyatu dengan kehidupan masyarakat dalam diskursus hadis dapat dipastikan terjadi karena dua sebab pokok, berkaitan dengan teologi-normatif dan tidak terlepas dengan kajian ilmu pengetahuan (saitifik).Kata Kunci: Hadis, gempa bumi, pandangan teologi dan saintifik